Meta organizacional e seus efeitos no comportamento de produzir do individuo - (:unkn) unknown (Universidade Federal de Goiás, 2018)
Behavior Analysis is one of the scientific fields that has dealt broadly with the concepts based on the behavior of the individual, and which has been the fruit of studies that can make possible the understanding of the behavior of workers' production in organizational environments. Three articles were produced to investigate the effect of the independent variables, goals as rules with characteristics of establishing operations and goals as rules with characteristics specifying discriminative stimuli. The objective of study 1 is to analyze the effect of goal setting on production behavior and whether its specifying characteristics have distinction. While study 2 seeks to verify if the goal setting parameters is able to raise the brace production behavior, and aims to verify the effect of establishing the goal based on the individual, while the other parameter is based on the group. Finally, article 3 seeks to respond to the limitations of the two previous articles regarding the complexity of the task, since the participant is allowed to choose the order of confection between the four techniques of bracelets available, having as instruction that the participant have to make at least one bracelet of each technique taught. The purpose of the third article is to answer if the participants chose to make the bracelets considered easier or more difficult. The research was carried out with 20 university students who were divided in 4 groups with 5 participants each, combined with the independent variables. For the accomplishment of the experiment, the participants were submitted to two stages. Being the first stage destined to the training of the four techniques of bracelets. The second step, after all participants had already learned how to make the four bracelet techniques, was used to apply the independent variables pertinent to this study.
Organizational goal and its effects on the producing behavior of the individual
Keywords: Metas; Estabelecimento de metas; Comportamento governado por regras; Regras; Análise do comportamento; Goals; Setting goals; Behavior governed by rules; Rules; Behavior analysis; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO